PERSEPSI SISWA PADA PENERAPAN MODEL TGT DALAM PEMBELAJARAN PKN PADA SISWA KELAS III SDN 36 PALEMBANG - Sari Irma Wati; Muhamad Idris; Nugroho Notosutanto Arhon Dhony (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The TGT (Team Game Tournament) learning model is an academic tournament that uses quizzes to determine individual student progress using a point system where students are selected as representatives of the group. This study aims to determine students' perceptions of the application of the TGT learning model in PKN learning. This research method uses a descriptive quantitative approach with data collection techniques through observation, questionnaires and interviews. The subjects of this study were all 28 students in grade III. The results of the study showed that the teams games tournament learning model was able to explore students' perceptions in PKN learning. This is indicated by some students stating that learning becomes more interesting, effective, and easy to understand. In addition, this learning model also encourages students to be more creative, active in discussions, and this study also shows that students who have high academic abilities tend to have a more positive perception of the TGT model. Based on the results of the questionnaire, 90% of students expressed positive perceptions of the teams games tournament learning model in PKN learning. Therefore, based on the results of the study, it is recommended that teachers can continue to develop and apply the teams games tournament model in PKN learning to increase student motivation and participation